Brief Report: The Ability of the 2013 American College of Cardiology/American Heart Association Cardiovascular Risk Score to Identify Rheumatoid Arthritis Patients With High Coronary Artery Calcification Scores. Issue 2 (February 2015) - Kawai, Vivian K.; Chung, Cecilia P.; Solus, Joseph F.; Oeser, Annette; Raggi, Paolo; Stein, C. Michael
<x xml:space="preserve">Abstract</x> Objective Patients with rheumatoid arthritis (RA) have increased risk of atherosclerotic cardiovascular disease that is underestimated by the Framingham Risk Score (FRS). We undertook this study to test the hypothesis that the 2013 American College of Cardiology/American Heart Association (ACC/AHA) 10‐year risk score would perform better than the FRS and the Reynolds Risk Score (RRS) in identifying RA patients known to have elevated cardiovascular risk based on high coronary artery calcification (CAC) scores. Methods Among 98 RA patients eligible for risk stratification using the ACC/AHA risk score, we identified 34 patients with high CAC (defined as ≥300 Agatston units or ≥75th percentile of expected coronary artery calcium for age, sex, and ethnicity) and compared the ability of the 10‐year FRS, RRS, and ACC/AHA risk scores to correctly assign these patients to an elevated risk category. Results All 3 risk scores were higher in patients with high CAC (P < 0.05). The percentage of patients with high CAC correctly assigned to the elevated risk category was similar among the 3 scores (FRS 32%, RRS 32%, ACC/AHA risk score 41%) (P = 0.223). The C statistics for the FRS, RRS, and ACC/AHA risk score predicting the presence of high CAC were 0.65, 0.66, and 0.65, respectively. Conclusion The ACC/AHA 10‐year risk score does not offer any advantage compared to the traditional FRS and RRS in the identification of RA patients with elevated risk as determined by high CAC. The ACC/AHA risk score assigned almost 60% of patients with high CAC to a low risk category. Risk scores and standard risk prediction models used in the general population do not adequately identify many RA patients with elevated cardiovascular risk.